2013
DOI: 10.3920/wmj2013.1563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bright greenish yellow fluorescence test as a screening technique for aflatoxin-contaminated maize in Malawi

Abstract: The bright greenish yellow fluorescence (BGYF) test has been used with varying success in screening for aflatoxins in maize. This test was applied to 180 maize samples collected from different markets within 12 districts of Malawi in order to evaluate its performance against high performance liquid chromatographic analysis. The number of BGYF grains in 2.5 kg unground samples ranged from 0 to 35 and about 49% of all tested samples had aflatoxin ranging from 1 to 382μg/kg. A total of 65(36%) of the examined ung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Although a significant proportion of the aflatoxin positive samples included in the study originated from the mid-elevation agro-ecological zone (22.5 %), it is worth noting that this does not reflect the aflatoxin prevalence in the zone as at all times, the majority of the samples that were tested were collected from the mid-elevation which is the main maize and groundnuts-producing area in Malawi. In fact, the aflatoxin problem is more prominent in the lower Shire and the lake shore, middle, and upper-Shire agro-ecological zone than in the midelevation and highlands (Matumba et al 2013;Matumba et al 2014b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a significant proportion of the aflatoxin positive samples included in the study originated from the mid-elevation agro-ecological zone (22.5 %), it is worth noting that this does not reflect the aflatoxin prevalence in the zone as at all times, the majority of the samples that were tested were collected from the mid-elevation which is the main maize and groundnuts-producing area in Malawi. In fact, the aflatoxin problem is more prominent in the lower Shire and the lake shore, middle, and upper-Shire agro-ecological zone than in the midelevation and highlands (Matumba et al 2013;Matumba et al 2014b).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the European Commission (Decision 2002/657/EC) calls for a ≤5 % false-negative rate for a screening technique to be acceptable (European Commission EC 2002). Previously, Matumba et al (2013) reported to have successfully screened shelled maize using the presence ≥four bright greenish-yellow fluorescence (BGYF) grains per 2.5-kg maize sample as an indicator for total aflatoxin >10 μg/kg with a 4.4 % falsenegative rate.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of A. flavus invasion in maize grain was assessed using the bright greenish yellow fluorescence (BGYF) test (Busboom and White, 2004; Matumba et al, 2013). After shelling and drying (as described above), 100-kernel random samples were taken for each plot.…”
Section: Methodsmentioning
confidence: 99%
“…Although there has been a gradual improvement, sub-Saharan Africa has been persistently ranked highest in human undernourishment worldwide with rates estimated between 31% in and 25% in 2011-2013(FAO, IFAD and WFP, 2013. Given the clear evidence of food shortage and high incidence of mycotoxin in food in Africa (Matumba et al, 2014;Adetunji, et al, 2014;Ediage et al, 2014;Mohale et al, 2013;Matumba et al, 2013;Lewis et al, 1995), is there any room for reaching a compromise between achieving food sufficiency and food safety in Africa? …”
Section: Toxicological Data On Mycotoxinsmentioning
confidence: 98%